Association, among very‐low‐birthweight neonates, between red blood cell transfusions in the week after birth and severe intraventricular hemorrhage. Issue 1 (14th May 2013) - Christensen, Robert D.; Baer, Vickie L.; Lambert, Diane K.; Ilstrup, Sarah J.; Eggert, Larry D.; Henry, Erick
<x xml:space="preserve">Abstract</x> Background Previous reports describe a statistical association, among very‐low‐birthweight (VLBW, <1500 g) neonates, between red blood cell (RBC) transfusion in the first days after birth and development of severe intraventricular (brain) hemorrhage (IVH). Study Design and Methods We hypothesized that after we established a neonatal intensive care unit (NICU) transfusion management program in 2009, a decrease in early (first week after birth) RBC transfusion rate and a decrease in the incidence of severe IVH occurred concomitantly. Results During a 9‐year period 2716 VLBW neonates were admitted to our NICUs. In 2004, 58% of VLBW neonates received one or more RBC transfusions during the first week. After a transfusion compliance program was established in 2009, this rate declined, reaching 25% by 2012. In parallel, the severe IVH rate also declined, from 17% in 2004 to 8% in 2012 (R2 = 0.73). IVH occurred in 27% of those who received a RBC transfusion during the first week versus less than 2% of those with no early transfusion (p < 0.001). The decrease in IVH rate occurred exclusively among neonates born in an Intermountain Healthcare perinatal center and not among those initially cared for in an "outside" hospital and subsequently transported to an Intermountain NICU. Conclusions It remains unclear whether transfusing VLBW neonates during the first days after birth is a proximate cause of IVH. However, the present report is consistent with previous studies showing that successful efforts to reduce early RBC transfusions is associated with a decrease in the incidence of severe IVH.